The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.4315/0362-028x.jfp-12-519
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH, Sodium Chloride, and Curing Salt on the Infectivity of Toxoplasma gondii Tissue Cysts

Abstract: Toxoplasma gondii is one of the most common zoonotic parasites in the world. The parasite causes no or mild symptoms in immunocompetent humans. However, a high potential hazard exists for seronegative pregnant women and immunocompromised patients. The consumption of meat containing tissue cysts or oocyst-contaminated vegetables and fruits or the handling of cat feces poses a high risk of infection with T. gondii. It is known that raw minced meat, raw fresh sausages, and locally produced raw meat products are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…To examine the effect of curing on the viability of cysts, a 50 g block of meat (5 × 4 × 3 cm) was soaked or rubbed with 2.0 or 6.0% NaCl and/or nitrite-enriched curing salt (NSC, NaCl enriched with 5% sodium nitrite, 10% potassium nitrate; New Shouso, Chiyoda Industry, Tokyo) for up to 7 days according to the study of Pott et al . [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…To examine the effect of curing on the viability of cysts, a 50 g block of meat (5 × 4 × 3 cm) was soaked or rubbed with 2.0 or 6.0% NaCl and/or nitrite-enriched curing salt (NSC, NaCl enriched with 5% sodium nitrite, 10% potassium nitrate; New Shouso, Chiyoda Industry, Tokyo) for up to 7 days according to the study of Pott et al . [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…There is likely to be an evolutionary trade-off between the growth-enhancing effects of MAF1b expression and the proinflammatory response that it induces. While induction of higher levels of inflammation may serve to reduce parasite growth and dissemination, it can also lead to death of the host ( 32 ), an endpoint in T. gondii infection that is likely maladaptive given the fact that T. gondii tissue cysts are not environmentally stable ( 33 , 34 ). Type II parasites (which are naturally HMA − ) activate the NF-κB pathway via the secreted protein TgGRA15 ( 35 ), which leads to the activation of inflammatory and antiapoptotic pathways ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…(47) The negligible risk of infection from salt-cured meat products consumed in Italy is consistent with several in vitro studies that confirmed that, despite the variability of the manufacturing parameters, T. gondii is not able to survive in such products due to a relatively high concentration of NaCl combined with a prolonged curing period. (48)(49)(50) Similarly, some researchers who investigated the viability of T. gondii were not able to isolate the parasite from 6, 12, and 40 dry-cured hams obtained from experimentally infected pigs, and consequently speculated that these products pose a very low risk. (43,51,52) However, these results are in contrast with other studies that reported the finding of viable T. gondii in dry-cured ham sampled at retail level (up to 4.8% of the samples).…”
Section: Discussionmentioning
confidence: 99%